(untitled) (Research, Society and Development, 2019)
The purpose of this research is to analyze aspects that relate to the teacher PhD’s constitution in the Legal Amazon in the 21st century. With this, we try to talk about the academic and experiential formations, to discuss about the advantages and difficulties of becoming a PhD, as well as to discuss some points that indicate the attitudes, postures, actions and practices that the teacher in education must assume before the amazonian realities. We performed a qualitative research, considering that the focus of this investigation is in the entire process of its construction and not only in the results obtained. We also developed a bibliographical research in books and scientific articles related to the theme, considering the contribution of diverse authors. In this way, we have shown that the teacher PhD’s constitution in this century is a continuous and complex process, which encompasses formations, knowledge, practices, skills, abilities, attitudes and utopias that promote transformational movements in the different contexts of amazonian spaces. We also understand that even with the difficulties that involve the teacher’s performance nowadays, the social contribution and its representation are still points that help in the satisfaction of being a teacher PhD in the Amazon.